The Legal Framework of Mergers as a Pillar of Economic Reform: A Normative Analysis of the Implementation and Coordination of Regulations - Afan Aftory (Publikasi Indonesia, 2025)
Business restructuring through mergers is a commonly used corporate strategy to increase efficiency, expand markets, and strengthen competitiveness. However, in the Indonesian context, the merger process does not only have economic considerations, but also a complex legal aspect because it involves various regulations, supervisory institutions, as well as the protection of minority shareholders and business competition. This article aims to analyze the legal framework governing mergers in Indonesia and evaluate its implementation effectiveness through comparative analysis with the United States and Singapore regulatory systems, with a focus on identifying regulatory gaps and formulating policy recommendations for strengthening merger laws. The article uses a normative-empirical juridical approach by examining laws and regulations, doctrines, and decisions of supervisory institutions (ICC and OJK), and comparing them with secondary data from actual merger case studies. The results of the study show that although the legal framework for mergers in Indonesia has been quite comprehensive, the Limited Liability Company Law, the Business Competition Law, and OJK regulations still have challenges in terms of information disclosure, protection of minority shareholders, and synchronization between authorities. This study recommends harmonization of regulations between supervisory agencies and strengthening legal due diligence in every merger process to ensure legal certainty and protection of the public interest.